Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1097/00007435-200007000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hormonal Contraception and Cervical Ectopy as Measured by Computerized Planimetry to Chlamydial Infection in Adolescents

Abstract: Using a new, reliable, and standardized technique to quantify cervical ectopy, the authors did not find an elevated prevalence of chlamydial infection in adolescents with cervical ectopy. Depot-medroxyprogesterone acetate use may increase the risk of chlamydial infection compared with combined estrogen-progestin oral contraceptives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 15 publications
1
18
2
Order By: Relevance
“…In another four cross-sectional studies 10,11,33,34 and in one clinical trial, 35 this association was maintained in multivariate analyses. A further two crosssectional studies 36,37 showed that this association disappeared in the multivariate analysis and a cohort study 38 found a strong tendency towards an association but did not reach significance.…”
Section: Chlamydia and Gonococcusmentioning
confidence: 96%
“…In another four cross-sectional studies 10,11,33,34 and in one clinical trial, 35 this association was maintained in multivariate analyses. A further two crosssectional studies 36,37 showed that this association disappeared in the multivariate analysis and a cohort study 38 found a strong tendency towards an association but did not reach significance.…”
Section: Chlamydia and Gonococcusmentioning
confidence: 96%
“…Pregnancy itself induces hyperplasia of the columnar epithelium and glands, hyperemia, and stromal edema, which could influence HIV susceptibility. 56,57 Vaginal cytokine profiles differ between pregnant and non-pregnant women, and it has been postulated that these fluctuations in inflammatory markers during pregnancy may account for an increased risk of HIV infection. 58,59 This finding suggests that the lower genital tract secretions of pregnant women are capable of potent anti-HIV activity.…”
Section: Pregnancymentioning
confidence: 99%
“…The increased risk of HIV acquisition among women using hormonal contraception has been noted in some [66,67], but not all [68][69][70][71] studies. High levels of oestrogen and progesterone during pregnancy or from exogenous sources could, in theory, affect vulnerability to HIV by inducing structural changes in the genital mucosa [72,73] or by immunological effects [74,75]. Limited evidence suggests that potential immunological pathways include the hormone-induced overexpression of coreceptors associated with HIV infection [76] or increased mucosal lymphoid aggregates [77].…”
Section: Vaginal Practices and Hiv Acquisitionmentioning
confidence: 99%
“…Limited evidence suggests that potential immunological pathways include the hormone-induced overexpression of coreceptors associated with HIV infection [76] or increased mucosal lymphoid aggregates [77]. Raised oestrogen levels are also associated with cervical ectopy, which exposes the more susceptible columnar epithelium to pathogens, and has previously been associated with approximately a two to threefold increased susceptibility to HIV infection [7,72,75,78]. In addition to these potential biological mechanisms, the use of condoms generally decreases whenever prevention of pregnancy is no longer a motivation, such as in women receiving hormonal contraception, or among pregnant and postpartum women [79][80][81].…”
Section: Vaginal Practices and Hiv Acquisitionmentioning
confidence: 99%